Autosomal dominant transmission of gouty arthritis with renal disease in a large Japanese family. Issue 2 (February 1991) - Yokota, N; Yamanaka, H; Yamamoto, Y; Fujimoto, S; Eto, T; Tanaka, K
Abstract : Six generations of a Japanese family had gouty arthritis and progressive nephropathy. Data on nine of 51 women (18%) and 15 of 66 men (23%) with either asymptomatic hyperuricaemia, gouty arthritis, or renal insufficiency were obtained. Renal function in four men and one woman with hyperuricaemia or gouty arthritis was also examined. Urinary excretion of uric acid was decreased in all subjects examined, including the young. Erythrocyte phosphoribosylpyrophosphate synthetase and hypoxanthine-guanine phosphoribosyltransferase activities determined in 10 patients were normal. Some patients had been treated with allopurinol to reduce serum uric acid concentrations, but the treatment did not prevent progression of renal impairment. Transmission of the disease in this large family is considered to be autosomal dominant. The data suggest that the disease in this family is the same entity as that described by other workers–that is, familial urate nephropathy. As far as is known this is the largest family with this disease so far reported.